The Business environment - Palmer, Adrian; Hartley, Bob ([New York] : McGraw Hill Education, 2002)
This textbook introduces students to business by exploring the dynamics of the business environment. It demonstrates the effects of these dynamics on business organisations and illustrates how decisions are made within organisations.
Part 1. Contexts -- Part 2. Looking inwardly at organizations -- Part 3. Element of the external business environment -- Part 4. Bringing it together: Environment analysis
Includes index.
Keywords: BUSINESS